Pneumococcal vaccine and HIV infection: report of a vaccine failure and reappraisal of its value in clinical practice. Issue 2 (April 1995) - Willocks, L J; Vithayathil, K; Tang, A; Noone, A
Abstract : A clinical failure of pneumococcal vaccine is reported. A 22 year old African woman was given 23-valent pneumococcal vaccine at her initial presentation with HIV infection. She was asymptomatic and had a CD4+ lymphocyte count above 500 cells/mm3. Eighteen months later she died of meningitis and septicaemia due to Streptococcus pneumoniae type 9 (an antigen included in the 23-valent vaccine). Pneumococcal antibody levels performed on stored blood demonstrated no serological response to the vaccine. This is the first reported case of clinical failure of pneumococcal vaccine in an HIV infected patient who received vaccine whilst at the asymptomatic stage of HIV infection and with relatively intact immune function. The literature pertaining to pneumococcal vaccination in the context of HIV infection was reviewed. Pneumococcal vaccination is recommended for HIV positive patients in the UK by the Departments of Health. It is likely that many physicians are not aware of these recommendations or are concerned about the poor efficacy of the vaccine, and it may consequently be underused in clinical practice. But the potential gain to the HIV positive patient is such that the vaccine should be offered to all HIV positive patients as soon as they present for medical care, irrespective of the stage of HIV disease. Physicians and patients should be aware that the vaccine is not fully protective and that episodes of sepsis, pneumonia and meningitis could still be pneumococcal in origin and should be treated appropriately. Awareness of the substantial risks of pneumococcal disease in HIV infected patients with prompt diagnosis and effective treatment is the most important strategy to decrease morbidity and mortality.